Fauna and biotope distribution of mites (Acari: Mesostigmata) from nest of the sand martin (Riparia riparia (Linnaeus, 1758)) in the territory of the Saratov oblast - Kondratev, Evgenii Николаевич; Anikin, Vasilii V. (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология)
The basis for the article was entomological collections from the nests of the sand martins (Riparia riparia (Linnaeus, 1758)) collected in the Saratov oblast in 2019–2022. A total of 12 colonies were examined in the Voskresensky, Krasnoarmeysky, Lysogorsky, Rivne, Engelssky and Khvalynsky districts of the Saratov oblast, as well as in the city of Saratov. Gamasid mites were collected using a Tullgren funnel for two to three hours and then identifi ed. In each of the studied colonies, a soil section was laid and its morphological description was carried out. As a result of studies of the fauna of gamasid mites in nests, 21 species from 10 families were identifi ed (Laelapidae, Haemogamasidae, Ascidae, Ologamasidae, Ameroseiidae, Dermanyssidae, Macrochelidae, Melicharidae, Pachylaelapidae, Rhodacaridae). The largest numbers and species diversity are characterized by colonies located in residual carbonate chernozem on limestone (12 species, 6719 specimens), the smallest in a colony located in dark chestnut soil on sand (3 species, 339 specimens). The dominant group consists of 3 species: Androlaelaps casalis (Berlese, 1887) – ectoparasite, obligate nest-dwelling mites, Stratiolaelaps miles (Berlese, 1892) and Hypoaspisella lubrica (Oudemans & Voigts, 1904) – free-living gamasid mites, facultative nest-dwelling mites